Cerebral hyperperfusion after flow diversion of large intracranial aneurysms. (16th November 2012) - Chiu, Albert Ho Yuen; Wenderoth, Jason
Abstract : Cerebral hyperperfusion syndrome has been proposed to be caused by rapidly increased blood flow into chronically hypoperfused parenchyma with resultant impaired autoregulation, and has been noted after clipping of intracranial aneurysms and carotid stenting. The occurrence of the syndrome after endovascular flow diversion, however, has not been previously described. A 52-year-old woman was admitted electively for flow diverter treatment of a recurrent ventral paraclinoid aneurysm arising within a dysplastic segment of the left internal carotid artery. During the immediate postprocedural period the patient was found to have confusion, right hemiparesis, facial droop and dysarthria, which resolved with blood pressure control. Subsequent CT perfusion on day 11 demonstrated mildly elevated cerebral blood flow, cerebral blood volume and permeability values in the left hemisphere.